Perubahan Fonem Kata Serapan Bahasa Inggris dalam Bahasa Indonesia dan Bahasa Korea: Analisis Kontrastif - Maria Tricia (Universitas Gadjah Mada, 2026)
Loanwords commonly undergo various forms of modification when they are adopted from one language into another. These modifications may involve changes in meaning, phonemes, or other linguistic elements. This article focuses on the phoneme changes found in English loanwords borrowed into Korean and Indonesian and aims to identify the differences between the two languages. The analysis is conducted through contrastive analysis by comparing the phoneme change patterns that appear in Korean and Indonesian loanwords derived from English. The findings reveal several types of phoneme changes in both languages, including vowel modification, consonant modification, phoneme addition, and phoneme omission. In Indonesian, the most frequent changes are vowel modification and phoneme addition, whereas in Korean the dominant patterns include vowel modification, consonant modification, and phoneme addition. The study also shows that some phoneme changes are shared by both languages, while others are language-specific. In addition, the overall patterns of adaptation differ between the two. Indonesian tends to adopt English loanwords more closely according to their written forms, while Korean more often reflects the pronunciation of the original words, although these forms are adjusted to fit the Korean phonological system.